A Total systems study on the Ninoy Aquino Parks and Wildlife Nature Center (NAPWNC) - Deriada, Gerard John; Funesto, Lim; Gutierrez, Isa Fe Teodorica B.; Ng, Lydia W. (College of Engineering, 2002)
The Ninoy Aquino Parks and Wildlife Nature Center is a government-sponsored nature reserve located in the heart of Quezon City. Its presence there is part of the Protected Areas and Wildlife Bureau?s efforts to promote awareness of the condition of our environment. The objective of the study is to perform a total systems study of the park?s organization that results in recommendations regarding improvements that can be made to the facilities, specially focusing on increasing the number of park visitors and preparing the park for an influx of visitors. The study is composed of three parts ? the marketing study, the technical study, and the financial study. For the marketing study, a survey was conducted an Analysis of Variance (ANOVA) was used as the tool to interpret the results. The results were that all factors considered ? medium used for advertising, place of residence, age and purpose of visit to NAPWNC ? affects the decision of individuals to go to the park or not. From here, the target market and the marketing strategy were derived. In the technical and financial studies, recommendations as to what additional facilities are needed and asked for by park visitors, such as reviving the children?s playground by adding swings and cleaning of the lagoon. The financial statements of the park were studied to determine what percentage of the budget was allotted to land improvements. An implementation strategy was also suggested with the main criteria for categorizing the recommendations being the impact to the environment, costs incurred and difficulty of implementation among others. It is recommended that further studies be made at certain stages of the implementation to determine the appropriateness of the succeeding steps and evaluate if the past projects have been set up properly